Investigation on surface roughness of mild steel using coated carbide cutting tools - Mohamad Rais, Ramli (2009)
This paper presents an investigation on surface roughness of mild steel operation using coated carbide cutting tools. There are three objective of this project that needs to be accomplished. First is to investigate the effect of various cutting condition for surface roughness and second is to find the factors or variable that mostly affects the surface roughness of mild steel. Comparing the surface roughness value between exact experiment and prediction is the last objective that must been done. The work piece is been turning for 9 parts due to 9 experiment for each cutting parameters that had been set before. After gathered all data or value that needed, two analysis are been performed. From the ANOVA analysis, the cutting speed is proving to be the most affect variable than depth of cut. The P-value indicated that cutting speed is significant than depth of cut with using 95% confident intervals. The analysis from ANOVA also indicated the best parameter use for turning at 50mm diameter mild steel. The results from multiple regression analysis shows that the predicted value almost same with experimental value, means the equation generated is 95 % accuracy.